Pengembangan Sistem Penghitung Langkah Kaki Hemat Daya Berbasis Wemos D1 Mini - Mhd. Idham Khalif; Dahnial Syauqy; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Foot calculate or pedometer is a tool to needed for a person frequent or hobby gym walking. As is foot steps calculate tool, user can be know ability and how many a person can do the steps.This system foot steps calculate able for calculate foot steps when walking, and then system can be power saving based on condition user. In this system foot steps calculate, be equipped with accelerometer sensor capable detection acceleration resulting from user foot steps, and then sensot datas will be processed using wemos d1 mini and also is wi- fi modul, will be to connected system with smartphone. If user not stepped, system can be power saving and can be normal, if user stepped again. This system able to calculate foot steps with accuracy achieve 100% and able to saving power amount 65,35%.